Development of a Salmonella cross-protective vaccine for food animal production systems. Issue 1 (1st January 2015) - Heithoff, Douglas M.; House, John K.; Thomson, Peter C.; Mahan, Michael J.
Highlights Development of a Salmonella cross-protective vaccine for livestock production. Salmonella dam vaccines are safe in the animal and the environment. Second generation Salmonella dam vaccines exhibit improved safety.